Adropin and Irisin Deficiencies Are Associated With Presence of Diagonal Earlobe Crease in CAD Patients - Wei, Na; Zhang, Ronghuai; Zhu, Zhanfang; Li, Rui; Yu, Qi; Wang, Qingyu; Xu, Cuixiang; Ma, Meijuan; Mu, Shengzhi; Liu, Fuqiang; Wang, Junkui (Frontiers in Cardiovascular Medicine, 2021)
Background and Aims: Diagonal earlobe crease (ELC) has been considered a potential cutaneous marker of atherosclerosis. However, the potential mechanism by which ELC and atherosclerosis are linked has not been adequately defined. Roles of adropin and irisin, novel biomarkers of endothelial function, in ELC have not been well-studied. This study aimed to test whether individuals with ELC are deficient in adropin and irisin, a characteristic that would likely promote endothelial dysfunction and provide a plausible common pathological basis for atherosclerosis and ELC. Methods: Patients diagnosed with coronary artery disease (CAD) with (n = 45) and without (n = 45) ELC were consecutively enrolled in the study. The ages of the patients enrolled ranged from 40–70 years. Other patients (n = 45) without ELC or CAD were recruited as the control group. All patients underwent coronary angiography. Serum adropin and irisin concentrations were assessed via enzyme-linked immunosorbent assay. Results: Circulating levels of irisin in the ELC group were significantly lower than those in the non-ELC group, and were highest in the control group. Serum adropin levels of the ELC group were significantly lower than those of the non-ELC group (P < 0.001). Interestingly, although the serum adropin level of the control group was greater than that of the non-ELC group, the difference failed to achieve statistical significance. In subgroup analysis of CAD and ELC, both serum adropin and irisin levels of the CAD and ELC groups were lower than those of the control group (P < 0.001). Receiver-operating characteristic curve analysis revealed that adropin and irisin have similar prognostic power for CAD and ELC. Conclusions: Low adropin and irisin were significantly associated with CAD and ELC. The deficiencies in adropin and irisin may be a common cause of both atherosclerosis and ELC, which explains why patients with ELC are prone to CAD.